Eight Years of Antimicrobial Stewardship Program (ASP) at a Large Academic Medical Center: Antibiotic Utilization, Hospital-onset Clostridium difficile infection (HO-CDI) and Resistance Trends. (4th October 2017) - Dubrovskaya, Yanina; Stachel, Anna; Inglima, Kenneth; Siegfried, Justin; Jen, Shin-Pung (Polly); Pham, Vinh; Aguero-Rosenfeld, Maria; Phillips, Michael
Abstract: Background: Antibiotic (ABX) use and outcome measures (rate of HO-CDI, local antimicrobial resistance) are recommended ASP metrics. These metrics can be used for internal benchmarking to assess ASP performance within an institution over time. Methods: An adult ASP at our 750-bed academic medical center was implemented in 2008. ASP interventions include prospective audit and feedback, prior authorization with fluoroquinolone (FLQ) restriction as an ASP target and implementation of facility-specific guidelines for common infections. Newer ASP initiatives were Cepheid/Xpert for blood cultures with Gram-positive cocci in pairs and clusters with daily real-time ASP interventions (11/2014), oral vancomycin secondary prophylaxis for patients with prior CDI (4/2014) and optimization of β-lactam (BL) dosing (piperacillin-tazobactam [PTZ] extended infusion hospital-wide 4/2013; cefepime [CEF] 4/2015 and meropenem 7/2015 protocols). ABX use is measured in days of therapy per 1000 patient-days (DOT/1000 PD) and length of therapy/admission when ABX were administered (LOT/ADM). NHSN definition is used for HO-CDI. For resistance trends the first unique isolate/patient/year regardless of source or susceptibility profile was included. Statistical analysis of trends during 8-years period 2009–2016 was performed by Poisson (SAS). Results: Major shifts in ABX use include decrease in FLQ use (-17%, P < 0.01) with compensatory increase in ceftriaxone (CTX, +12%, P < 0.01), antipseudomonal BL (+3%, P < 0.01) and no change in carbapenem (+0.6%, P =0.5) as well as an increase in nafcillin and oxacillin (+7%, P < 0.01) use. There was a decrease in aggregate LOT/ADM (-4%, P < 0.01) with no change in DOT/1000 PD. We observed a decrease in HO-CDI rate (-17%, P < 0.01). Major resistance trends include reduction in Enterobacteriaceae spp. and Pseudomonas aeruginosa isolates nonsusceptible (NS) to FLQ (-4%, P < 0.01; -10%, P < 0.01, respectively) with increase in Enterobacteriaceae spp. NS to ceftriaxone, (+3%, P < 0.01). A decrease in P. aeruginosa NS to PTZ (-11%, P < 0.01) and no change for CEF was reported. There was no difference in Enterobacteriaceae spp. NS to PTZ or CEF. Conclusion: Overall, reported trends aligned with ASP initiatives. Increased CTX NS is of concern and warrants an ASP-led strategy to decrease CTX use. Disclosures: All authors: No reported disclosures.